Extreme Machines - Maynard, Christopher; Nang Chan Yeema (New York, USA DK publishing, Inc., 2000)
Presents some of the most powerful and unusual vehicles used today, including the dragster, rocket plane, and stretch limo.
Keywords: Juvenile Nonfiction